Impact of source variability on flexibility for demand response. (15th December 2021) - O'Connell, Sarah; Reynders, Glenn; Keane, Marcus M.
Abstract: This paper assesses the quality of the services provided for demand response by analysing the results of experimental work activating flexible sources in buildings, while evaluating the impacts on occupant comfort and extending the dataset through aggregation, to quantify the uncertainty for multiple systems. Power and energy flexibility is an integral part of the solution to address the challenge of grid balancing with increased renewable generation integration. However, the variability of the provided flexibility, as measured by the stability and consistency of load reduction or increase, may vary widely. To address this, the concept of quality of flexibility is introduced and analysed through the results of experiments conducted at a case study building to activate three sources of flexibility: heat pumps, Air Handling Unit fans and battery storage. The results show that fan data exhibits low uncertainty, suitable for ancillary services, whereas heat pumps' volatility is large. Standard error for heat pumps was within the quality threshold of 10 %, appropriate for energy services. Aggregation of multiple systems through the creation of a semi-synthetic dataset decreased the uncertainty for hourly energy services to as low as 2 %. For all cases, the impact on occupant comfort was not found to be significant. Highlights: Concept of quality of flexibility defined and analysed using statistical approaches. Experiments at a case study building using heat pumps and Air Handling Unit fans. Fans exhibited stable flexibility but heat pumps more suited to kWh energy services. Aggregation of multiple systems decreased hourly uncertainty to 2 %. Occupant comfort impacts were not found to be significant.